2022
DOI: 10.3389/fagro.2022.990869
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate solubilization and plant growth promotion by two Pantoea strains isolated from the flowers of Hedychium coronarium L.

Abstract: Phosphorus (P) is an essential macronutrient for plants and is considered as one of the limiting nutrients to plants. The majority of P in the soil is found in the form of insoluble phosphate complexes, making the P unavailable for plants. In the present study, we report two highly efficient phosphate solubilizing bacteria isolated from the closed flower of Hedychium coronarium L., a medicinal plant commonly known as Gulbakawali. Based on morphological, biochemical, and molecular characterization, the two bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The nitrogen-fixing and phosphate-solubilizing properties of the three isolates are recognized as important features in the agricultural soil system. Their ability to convert atmospheric nitrogen into ammonia [ 26 , 30 , 31 ], as well as insoluble inorganic phosphate compounds into available forms [ 26 , 55 , 56 ], plays a vital role in providing essential nutrients that living organisms can use for biosynthesis. Additionally, during the growth of our strains, cellulose degradation was also observed, facilitating the conversion of organic waste into valuable organic matter and contributing to the reduction of the C:N ratio while also enhancing soil productivity [ 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…The nitrogen-fixing and phosphate-solubilizing properties of the three isolates are recognized as important features in the agricultural soil system. Their ability to convert atmospheric nitrogen into ammonia [ 26 , 30 , 31 ], as well as insoluble inorganic phosphate compounds into available forms [ 26 , 55 , 56 ], plays a vital role in providing essential nutrients that living organisms can use for biosynthesis. Additionally, during the growth of our strains, cellulose degradation was also observed, facilitating the conversion of organic waste into valuable organic matter and contributing to the reduction of the C:N ratio while also enhancing soil productivity [ 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Beneficial microbes include bacterial, archaeal, and fungal communities. They promote plant growth by improving nutrient acquisition through solubilization of phosphate, increasing nitrogen availability from organic matter, and iron chelation by siderophore activity [ 57 , 58 ]. They also improve plant disease resistance by inducing phytohormones, production of antibiotics and fungal cell wall-degrading enzymes, and competition for iron uptake by siderophores [ 57 ] and increase tolerance to abiotic stress such as drought and salt and insect herbivory [ 59 , 60 ].…”
Section: Strawberry Microbiome Composition and Its Role In Plant Grow...mentioning
confidence: 99%
“…Moreover, many studies have found that endophytes serve as bio-stimulants to promote macro- and micronutrient uptake and translocation that ultimately modify phytohormones to improve plant growth [ 18 , 20 ]. Fungal endophytes can solubilize phosphate, generate phytohormones such as indole acetic acid (IAA), gibberellic acid (GA), and siderophore [ 21 , 22 ], and encourage plants to produce antioxidants, crucial for ROS scavenging [ 11 , 20 ].…”
Section: Introductionmentioning
confidence: 99%